A novel MPPT algorithm for load protection based on output sensing control - Hassani, M.; Mekhilef, Saad; Patrick Hu, A.; Watson, N.R. (2011)
This paper presents a novel maximum power point tracking (MPPT) algorithm for load protection based on output sensing control. All MPPTs are based on input sensing and there is a drawback in applications which load protection is essential. This drawback can be addressed by applying two more sensors at the output. However having two sensors at input side as well as two more at output will increase the size and cost of the controller. To address this drawback without the need to increase the number of sensors, a novel control system and tracking algorithm based on the output sensing control and P&O algorithm is proposed. The main difference of the proposed control system with existing systems is, moving the control sensors from input side to output side of controller and consequently, apart from providing MPPT algorithm, controller is also able to do load protection at the same time. To demonstrate how the system operates in normal MPPT mode as well as how it operates for the load protection, the system is tested with different resistive loads and the simulation results indicate the feasibility and improved functionality of the system.